ANALISA PENGARUH SUDUT HALUAN KAPAL SELF PROPELLED OIL BARGE (SPOB) 216 GT TERHADAP HAMBATAN DENGAN METODE COMPUTATIONAL FLUID DYNAMIC (CFD) - Rahman, Abdul Rohman; Rulianto, Jangka; Suranto, Wawan (Politeknik Negeri Madura, 2025)
This study aims to analyze the effect of bow angle variations on the total resistance of a 216 GT Self-Propelled Oil Barge (SPOB) using the Computational Fluid Dynamics (CFD) method. The efficiency of bow design significantly affects a vessel’s hydrodynamic performance, particularly at the cruising speed of 5 knots. In this research, three bow angle variations—49°, 42°, and 39°—were modeled and Holtrop Metode and CFD Metode . The simulation results show that bow angle modification has a significant impact on the ship’s resistance. The 39° bow angle yielded the lowest resistance at 3.995 kN, followed by 42° at 4.135 kN, and 49° at 4.241 kN, based on CFD simulation results. Therefore, the 39° bow angle is recommended as the optimal design for improving voyage efficiency and reducing fuel consumption.